Tribal women empowerment through entrepreneurship: evidence from Mayurbhanj District, Odisha - Naveen, S.; Parida, Jayanta Kumar; Panda, Itishree (Frontiers in Sociology, 2023)
Introduction Empowering women in a tribal context through entrepreneurship is an approach for enabling and making them economically and socially viable. This paper aims to highlight entrepreneurship in a specific tribal context and provide insight on some instances or cases relating to women's empowerment. Although there are many initiatives from international organizations and governmental institutions to support women entrepreneurs, especially tribal women, they suffer from isolation as a result of their language and lifestyle differ from the rest of society, which made the growth of their business and ability to compete arduous, and thus affected their ability to make various decisions in their lives. This study examines the pathway to a better understanding of increasing access to entrepreneurship for tribal women in Mayurbhanj district, Odisha. Methods The sample size was 111 Santhal tribal women entrepreneurs, and all of them were interviewed using an interview schedule and Focus Group Discussions (FGDs). Two analytical tools were used (a linear regression model to find which dependent variables influence entrepreneurs and the Women's Empowerment Index (WEI) to measure the progress in social and economic opportunities). The respondents was interviewed and asked on the various WEI indicators before and after an entrepreneurship intervention. Results and discussion It was observed through the results that the empowerment of women has changed in a positive direction after establishing their work; according to the indicators of the study, the Women's Empowerment Index has changed from 0.61 to 1.26. It was also found that entrepreneurship has a positive and significant impact on women's decision-making within the family, and therefore, it was suggested through research to increase the intervention from the government and related organizations with more initiatives that contribute to the possibility of increasing women's education and their financial ability to open new enterprises.